Evaluation of a hand-held electrical conductivity meter for detection of subclinical mastitis in cattle - Musser, Jeffrey M. B. (1998)
Objective To assess, under field conditions, whether a hand-held electrical conductivity (EC) meter could be used to detect subclinical mastitis caused by pathogens most commonly associated with mastitis in dairy cows. Animals 425 lactating cows on 15 dairies in Costa Rica. Procedure Immediately prior to milking, milk samples from each quarter were tested, using a hand-held EC meter. A milk sample from the quarter with the highest score was submitted for bacteriologic culture. Results of bacteriologic culture were compared with highest absolute EC score for each cow and with differential EC score (ie, difference between the highest and lowest absolute EC scores for the 4 quarters of each cow). Results Absolute EC score for cows with subclinical mastitis was significantly higher than that for cows without subclinical mastitis, and absolute EC score was significantly associated with detection of subclinical mastitis. If absolute EC score ≥ 7 was considered indicative of subclinical mastitis, sensitivity was 0.43, specificity was 0.83, predictive value of a positive result was 0.39, and predictive value of a negative result was 0.85. Differential EC score for cows with mastitis was significantly higher than that for cows without subclinical mastitis. If differential EC score ≥ 2 was considered indicative of subclinical mastitis, sensitivity was 0.53, specificity was 0.77, predictive value of a positive result was 0.37, and predictive value of a negative result was 0.87. Clinical Implications A hand-held EC meter may be used to screen cows for subclinical mastitis.